The Relationship of Self-Compassion in Facing Emotional Intelligence of College Students: Perspective of Korean movie 'When Life Gives You Tangerines' - Kusnia Nikmatul Khasanah; Surawan Surawan; Sarimah Awang (Multidisciplinary: Journal of Education an Learning, 2025)
University students often face emotional pressure due to academic demands and social expectations, making emotional regulation an essential skill. This study aims to explore the relationship between self-compassion and emotional intelligence among students, using the Korean drama When Life Gives You Tangerines as a reflective emotional context. The drama was selected for its strong depiction of self-compassion values relevant to students' emotional challenges. Using a quantitative correlational approach, the study involved 32 randomly selected students and utilized a Likert-scale questionnaire to measure both variables. Data analysis through Pearson Product-Moment correlation revealed a positive and significant relationship between self-compassion and emotional intelligence (r = 0.272; p = 0.028). Although the correlation falls within the low category, the result indicates that higher self-compassion is associated with better emotional understanding and regulation. These findings highlight the importance of fostering self-compassion as a foundational element in developing emotional intelligence and supporting students' psychological well-being.